24.6k views
1 vote
3(x - 4) = -3. Solve for x.

2 Answers

3 votes

Answer:

x = 3

Explanation:

Divide each term by 3 and simplify.

x - 4 =
(-3)/(3)

Cancel the common factor of 3 .

x - 4 = -1

Move all terms not containing x to the right side of the equation.

x = -1 + 4

Add -1 and 4.

x = 3

Hope this helps!

User Dave Clarke
by
5.3k points
4 votes

Answer:

x = 3

Explanation:

3(x - 4) = -3

Divide by 3

3/3(x - 4) = -3/3

x-4 = -1

Add 4 to each side

x-4+4 = -1+4

x = 3

User Yem
by
5.0k points